Female education and marriage in Pakistan: The role of financial shocks and marital customs - Sarah Khan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This project aims to explore the effect of wealth shocks on education and marriage for young women in Pakistan. Financial shocks are used to estimate the probability of dropping out of education and into marriage. Using the Pakistan Rural Household Panel survey for the years 2000-10, the effects of financial shocks on the probability of dropping out of education and into marriage are estimated for boys and girls in rural areas. Second, the returns to education in the marriage market are estimated using information on marital payments of dowry and brideprice. Lastly, the intergenerational effects of women's increased bargaining power due to marital assets is estimated. The results show wealth shocks do not have a gendered effect on school dropout. Also, adverse shocks during the teenage years do not increase the probability of early marriage. However, this relationship is negative in villages where marital payments are typically higher-that is, marriage costs can delay early marriage in shock-hit households as they are more creditconstrained. Lastly, higher educated women receive more marital assets, which can contribute to increased bargaining power within the marriage. This increased bargaining power also has intergenerational effects on children's schooling.
Keywords: C26; I26; J16; Q54; 330; marital payments; financial shocks; early marriage; school dropout; intergenerational effects